2014
DOI: 10.1111/ctr.12453
|View full text |Cite
|
Sign up to set email alerts
|

Conversion from calcineurin inhibitor–based immunosuppression to mammalian target of rapamycin inhibitors or belatacept in renal transplant recipients

Abstract: The calcineurin inhibitors (CNIs) remain the standard of care for maintenance immunosuppression following renal transplantation. CNIs have demonstrated their effectiveness in reducing acute cellular rejection; however, some evidence suggests that these compounds negatively affect native renal function and are associated with allograft injury in renal transplant recipients. CNIs have also been linked with hypertension, new-onset diabetes after transplantation, tremor, and thrombotic microangiopathy, which have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 73 publications
(106 reference statements)
0
11
0
1
Order By: Relevance
“…3,4 Some CNI-avoiding or CNI-minimizing immunosuppressive regimens, many involving the mammalian target of rapamycin (mTOR) inhibitors sirolimus and everolimus, have been evaluated in kidney transplant recipients. 5 In prospective studies, patients switching from CNI-based to mTOR inhibitor-based immunosuppression showed significant improvements in kidney function at 12 months postconversion versus patients who continue treatment with cyclosporine or tacrolimus. However, mTOR inhibitortreated patients are more likely to have adverse events (AEs), especially dyslipidemia and proteinuria.…”
mentioning
confidence: 99%
“…3,4 Some CNI-avoiding or CNI-minimizing immunosuppressive regimens, many involving the mammalian target of rapamycin (mTOR) inhibitors sirolimus and everolimus, have been evaluated in kidney transplant recipients. 5 In prospective studies, patients switching from CNI-based to mTOR inhibitor-based immunosuppression showed significant improvements in kidney function at 12 months postconversion versus patients who continue treatment with cyclosporine or tacrolimus. However, mTOR inhibitortreated patients are more likely to have adverse events (AEs), especially dyslipidemia and proteinuria.…”
mentioning
confidence: 99%
“…Eur J Gen Med 2016;13(3): [16][17][18][19][20][21][22] mmHg; P=0.04) in the SRL and Tac groups, respectively. At 36 month, the mean systolic blood pressure (132±19 and 141±21 mmHg; P=0.001) and diastolic blood pressure (74±14 mmHg and 82±10 mmHg; P=0.001) in the SRL and Tac groups, respectively.…”
Section: Blood Pressurementioning
confidence: 97%
“…Oral prednisolone was then given at a dose of 1 mg/ kg per day, and then gradually tapered down to 5 mg/day by the 3rd month post-transplantation. Tacrolimus was started at a dose of 0.075 mg/kg/day in two divided doses targeting Eur J Gen Med 2016;13(3): [16][17][18][19][20][21][22] a 12-h whole blood trough level of 10-15 ng/mL in the first 3 months and then from 3 to 7 ng/ml thereafter. Concomitant immunosuppression and other treatments (i.e.…”
Section: Immunosuppression Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…[161718] It may also have a role as an effective substitute for CNI therapy late after transplantation to avoid further CNI nephrotoxicity. [192021222324] However, the potential risk and benefit of this conversion strategy are not yet fully known, especially in the long-term.…”
Section: Introductionmentioning
confidence: 99%